Analysis of spectrum handoff schemes for cognitive radio networks considering secondary user mobility. (4th June 2020) - Preetha, K.S.; Kalaivani, S.
Cognitive radio has been proposed as an intelligent wireless communication system towards the usage of dynamic spectrum access in next generation networks, where the primary users (PU) and secondary users (SU) can share the spectrum, while causing minimum interference to each other. Spectrum mobility is the main element for the effective execution of cognitive radio networks. Spectrum mobility can be achieved by means of spectrum handoff (SHO). Initially, SUs continuously sense the channels to identify an idle channel. Error in sensing channel is possible. A detection theory is put forth to analyse the spectrum-sensing errors with the receiver operating characteristic (ROC) considering false alarm probability, missed detection and detection probability. Also, we meticulously investigate and analyse the probability of spectrum handoff (PSHO) with lognormal-3 and Hyper-Erlang distribution models considering SU call duration and residual time of spectrum holes availability designed for tele-traffic analysis.